Detection of serum human epididymis secretory protein 4 in patients with ovarian cancer using a label-free biosensor based on localized surface plasmon resonance - Yuan JL (Dove Medical Press, 2012)
Jialing Yuan,1 Ruiqi Duan,1 Huan Yang,2 Xiangang Luo,2 Mingrong Xi11Department of Gynecology and Obstetrics, West China Second University Hospital, Sichuan University, 2State Key Laboratory of Optical Technologies for Microfabrication, Institute of Optics and Electronics, Chinese Academy of Science, Chengdu, ChinaBackground: Detection of the human epididymis secretory protein 4 (HE4) biomarker plays an important role in the early diagnosis of ovarian cancer. This study aimed to develop a novel localized surface plasmon resonance (LSPR) biosensor for detecting HE4 in blood samples from patients with ovarian cancer.Methods: Silver nanoparticles were fabricated using a nanosphere lithography method. The anti-HE4 antibody as a probe, which can distinctly recognize HE4, was assembled onto the nanochip surface using an amine coupling method. Detection was based on the shift in the extinction maximum of the LSPR spectrum before and after the HE4-anti-HE4 antibody reaction. These nanobiosensors were applied to detect HE4 in human serum samples and compare them using an enzyme-linked immunosorbent assay.Results: Tests relating to the detection of HE4 demonstrated that the LSPR-based biosensor featured a fast detection speed, good specificity, effective reproducibility, and long-term stability. The linear range for LSPR was between 10 pM and 10,000 pM, with a detection limit of 4 pM. An excellent correlation between LSPR and enzyme-linked immunosorbent assay results was observed in human serum.Conclusion: This study is the first clinical diagnostic application of the LSPR biosensor in ovarian cancer. The LSPR biosensor, a rapid, low-cost, label-free and portable screening tool, can serve as a very effective alternative for the clinical serological diagnosis of ovarian cancer.Keywords: localized surface plasmon resonance system, nanobiosensor, ovarian cancer biomarker, serum HE4 protein